THE INFLUENCE OF LOCAL TAXES AND LEVIES ON LOCAL REVENUE OF BIREUEN DISTRICT - Intan Zuhra; Nanda Darisa; Rifa Muriza; Ella Rahmayanti (Universitas Efarina, 2022)
This study aims to determine the effect of local taxes and levies on local revenue, there are two variables, namely the independent variable of local taxes and levies and the dependent variable of local revenue. The method used in this research is descriptive and verification method with quantitative approach. This study uses secondary data, data analysis using multiple linear regression analysis. Hypothesis testing in this study used T test statistics with the help of the IBM SPSS Statistics 23.00 for Windows program. The results showed that local tax (X1) had a significant effect on local revenue (Y) and local retribution (X2) had no significant effect on local revenue (Y). Determination (R2 ) local taxes and local retribution influenced local revenue 67.1%, the remaining 32.9% influenced by other factors.